2019
DOI: 10.1108/hff-06-2019-0485
|View full text |Cite
|
Sign up to set email alerts
|

Numerical investigation of heat transfer of laminar and turbulent pulsating Al2O3/water nanofluid flow

Abstract: Purpose The purpose of this paper is to investigate the heat transfer of laminar and turbulent pulsating Al203/water nanofluid flow in a two-dimensional channel. In the laminar flow range, with increasing Reynolds number (Re), the velocity gradient is increased. Also, the Nusselt number (Nu) is increased, which causes increase in the overall heat transfer rate. Additionally, in the change of flow regime from laminar to turbulent, average thermal flux and pulsation range are increased. Also, the effect of diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
25
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(25 citation statements)
references
References 70 publications
0
25
0
Order By: Relevance
“…This parameter indicates the difference between the average cost of products and fuel due to the destruction and cost of investment. In this relationship, c P, k and c F, k are respectively the average cost per unit exergy of product and fuel for the component k, and their values are obtained from Equations (12) and (13).…”
Section: Exergoeconomic Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…This parameter indicates the difference between the average cost of products and fuel due to the destruction and cost of investment. In this relationship, c P, k and c F, k are respectively the average cost per unit exergy of product and fuel for the component k, and their values are obtained from Equations (12) and (13).…”
Section: Exergoeconomic Analysismentioning
confidence: 99%
“…4 They also studied different types of desalination systems and their governing equations, then modeled the energy consumption of the evaporation vacuum evaporation system with a brine tank and reported on the economic analysis results. [5][6][7][8][9][10][11][12][13] Ghaebi et al investigated the thermodynamic modeling (including energy and exergy analysis) and the exogeochemical study of a power and hydrogen generation system including an organic Rankine cycle and a proton exchange membrane electrolyzer driven by geothermal energy, with different operating fluids (R245fa, R114, R600, and R236fa) to compare their effects on the performance of the payment system and used EES software for this purpose. Their results showed that the operating fluid R245fa has the highest energy and exergy efficiency, which are 3.11% and 67.58%, respectively.…”
mentioning
confidence: 99%
“…The numerical outputs indicated that the derived formulation given in Equation 6exhibited better prediction performance compared to the comparative equation-4 (CE-4) and the comparative equation-5 (CE-5). Finally, from the numerical point of view, it is also noted that some useful recent investigations can be found in the field of thermal energy storage, 19 nanofluid flow, 20,21 low-fluid pressure safety valve design, 22 heat transfer, 23 and thermal analysis. 24…”
Section: Numerical Comparisonmentioning
confidence: 99%
“…A comparison of analytical and numerical methods of thermal analysis of rectangular cross-section porous fins enclosure was investigated by Hoseinzadeh et al [10,11]. Hoseinzadeh et al [12] have investigated numerically the heat transfer of a laminar and turbulent pulsating Al 2 O 3 /water nanofluid flow. The problem of free convective flow in a rectangular enclosure in the presence of four discrete heaters was investigated by Nithyadevi et al [13].…”
Section: Introductionmentioning
confidence: 99%